Numerical simulation and analytical study of glulam timber beams - Tsalkatidis, Themistoklis (International Journal of Engineering and Technology, 2014)
Glulam beams or glued-laminated beams consist of sawn lumber laminations (timber) bonded with an adhesive material. This paper, through the mathematical description of the contact conditions that apply at the interfaces of glulam beams and the development of two three-dimensional finite element models by the use of the ANSYS software package, studies the flexural properties of unreinforced (UGB) and reinforced (RGB) glulam beams. The first computational model presents an unreinforced glulam beam that has been produced by three wood laminations of dimensions 6 by 3.6 by 176 cm. The latter one describes a reinforced glulam beam, which has been produced by gluing a 0.15 cm thick steel plate at the bottom edge of the previously described beam. The computational analysis indicates that the two glulam beams have significantly different bearing capacities under the same load and support conditions. The failure mode of the UGB is brittle whereas the one of the RGB is ductile. The numerical results of both models are in close agreement with experimental ones from the international literature. Keywords: Glulam Timber Beams, Numerical Simulation, Contact.